The exorcism [videorecording (DVD)] - Miller, Joshua (Joshua Israel); Fortin, M. A. (Mark Alexandre), 1978-; Bensi, Danny; Crowe, Russell, 1964-; Simpkins, Ryan; Worthington, Sam, 1976-; Bailey, Chloe, 1998-; Goldberg, Adam, 1970-; Pasdar, Adrian, 1965-; Pierce, David Hyde (Vertical, 2024)
When troubled actor Anthony Miller begins unraveling while on the set of his latest horror film, his estranged daughter Lee questions if it's caused by his past addictions, or whether something darker is at play.